Neutrophil Extracellular Traps in Dengue Are Mainly Generated NOX-Independently - Garishah, Fadel Muhammad; Rother, Nils; Riswari, Silvita Fitri; Alisjahbana, Bachti; Overheul, Gijs J.; van Rij, Ronald P.; van der Ven, André; van der Vlag, Johan; de Mast, Quirijn (Frontiers in Immunology, 2021)
Neutrophil extracellular traps (NETs) are increasingly recognized to play a role in the pathogenesis of viral infections, including dengue. NETs can be formed through NADPH oxidase (NOX)-dependently or NOX-independently. NOX-independent NETs can be induced by activated platelets and are very potent in activating the endothelium. Platelet activation with thrombocytopenia and endothelial dysfunction are prominent features of dengue virus infection. We postulated that dengue infection is associated with NOX-independent NET formation, which is related to platelet activation, endothelial perturbation and increased vascular permeability. Using our specific NET assays, we investigated the time course of NET formation in a cohort of Indonesian dengue patients. We found that plasma levels of NETs were profoundly elevated and that these NETs were predominantly NOX-independent NETs. During early recovery phase (7-13 days from fever onset), total NETs correlated negatively with platelet number and positively with platelet P-selectin expression, the binding of von Willebrand factor to platelets and levels of Syndecan-1. Patients with gall bladder wall thickening, an early marker of plasma leakage, had a higher median level of total NETs. Ex vivo, platelets induced NOX-independent NET formation in a dengue virus non-structural protein 1 (NS1)-dependent manner. We conclude that NOX-independent NET formation is enhanced in dengue, which is most likely mediated by NS1 and activated platelets.